The phenomena of modern motherhood as a moral value: sociological aspect - Paulava, Katsiaryna H. (Journal of the Belarusian State University. Sociology, 2020)
The article consist a sociological review of the phenomena of modern motherhood as a moral value. The problem field for complex study of motherhood as a moral value is presented. Sociological indicators for empiric study are highlighted. Among them are: valuable characteristics of motherhood; the structure of mother’s self-awareness; mother’s representations about child; the role of mother’s image in child’s development; child’s attachment to mother. Feminist tradition levels motherhood as a self-value. Feminist tradition treats motherhood as a biological function, which interferes social, economic and politic functions of women. Contrary to feminist tradition, modern turbulent society is complicated for men. A woman is facing a new challenge, her role is to continue a man-kind, according to archetype of mother. This thesis should be transmited as a socialization model of young generation.